Critical Analysis of the Current Status of Transdisciplinary Research in Neonatology and Sustainable Development Goals - Muhammad Irfan-Maqsood (Iranian Journal of Neonatology, 2025)
Background: Neonatology, a discipline that deals with a variety of medical conditions such as prematurity, breathing, infections and birth defects, has seen rapid development and significant advancements during the past decades to ensure the survival and healthy life of newborns. Although the efforts of medical scientists following the multidisciplinary and interdisciplinary approaches have successfully reduced the neonatal mortality rate from about 5 million before 2000s to 2.3 million as of 2022, but stills challenges in understanding and addressing the complex neonatal health issues remain unsolved, which invites the necessity to apply complex and comprehensive transdisciplinary research approaches. Transdisciplinary research approaches are complex types of approaches applied for complex types of issues, engaging all stakeholders of society, so a holistic approach to understand the neonatal health, and the impacts of environmental, social, and biological factors should be studied. This article has shed light on the significance of transdisciplinarity which has proven its role in the development of a sustainable society and these holistic research approaches, can ensure meaningful results to reduce the mortality rate of newborns from 50% to 5%.